FORMASI MAUBISSE DAN AILEU DI BAGIAN BARAT TIMOR LESTE DALAM KERANGKA TEKTONOSTRATIGRAFI PULAU TIMOR - Syaiful Bachri (Pusat Survei Geologi, 2008)
The stratigraphic position of the Maubisse and Aileu Formations in Timor remains controversial despite the latest studies, which tend to place them within the para-autochthonous sequence. Field evidence indicates that the two formations have Â transitional relationships with the overlying para-autochthonous Wailuli Formation. Paleontological evidence also indicates that the Maubisse Formation was derived from the Australian continent, and the stratigraphically related Aileu Formation was located on the northwest flank of Australia until the Neogene arc- continent collision event.Â Keywords: Maubisse Formation, Aileu Formation,Wailuli Formation, tectonostratigraphy, para-autochthonous sequence.Â